A clínica com bebês: entre o discurso do risco e o laço com a parentalidade - Girardi, Ana Lúcia Franco Nobile (2008)
This doctorate thesis brings on a reflection on the clinic with babies prematurely born. That reflection derived from my professional path itself, in which, since 1994, I ve taken part of a central program of maternal-infantile attendance, the Kangaroo Mother Method, in a hospital of the interior of Sao Paulo State, Regional Hospital of Assis. The starting point of this work is the discussion of the phonoaudiologic clinic that operates by the risk notion, understood in the clinical environment as much as origin of disturbances, as well as parameter to measure a normal pattern of the organism. It is then as scale for the definition of the pathological that the risk notion acts in the phonoaudiologic practice; and it is exactly from this perspective that we stay away from. From the beginning, 14 years ago, the phonoaudiologic actions in clinic practice with babies have been linked to the parents, more specifically to the mother, since the maternal presence was needed in hospital during the baby s recovery period in order to reach the goals of the Kangaroo Mother Method. As a professional involved in that hospital project, was I affected not only by the movements of the premature birth, but by the parents speech that convey the significance of their encounter with their child as well, crucial data that produced effects in clinic practice. I understand that such practice caused my distance from the speech centered in the organic conditions of the premature, consequently engendering the bet in the decisive power of the language in the subjective structuring, i.e., in the strength of the speech as a possible source of a come-to-being subject of the human baby, acting as an anticipation position introduced by the bond of parenthood. In this work I aim at showing that the issues about clinic with babies, mainly those considered of risk activity bounded in the period of hospital internment and in the following accompaniment , are not being sufficiently discussed in the phonoaudiological field and in this sense I indicate an alternative direction, the establishment of the conjunction between the two moments of phonoaudiologic activity based in only one commitment, the premature body in an entrance process into the symbolic, through the effects of the language. The promoted discussions fit in this theorization about the Clinic of Language, under the coordination of Maria Francisca Lier- DeVitto and on Claudia Lemos thought; more precisely the structural and the unfolding reflection, starting from the Lacanian Psychoanalysis, in the statute of pulsing body. It has to be mentioned, however, that another step will be taken, the approach of the Lacanian Psychoanalysis starting with Freud that the clinic with babies will demand a theoretical effort on the subject in relation with parenthood